Traffic Engineering Analysis of One-Way System at Mambo Market Four-Way Intersection: A Case Majalengka - Moch Aris Risnandar; Muhamad Taufik; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2025)
The economic centre is a very important thing that is located in an area, as a result the area affected as an economic centre experiences congestion which results in time, energy and health being disrupted. As happened in the implementation of the one-way system at the simpang empat Pasar Mambo, which is one of the accesses to the economic centre in Majalengka. Congestion at the Simpang Empat Pasar Mambo is the most common traffic problem, particularly in the middle of the day because of the higher volume of traffic compared to other times. This study set out to assess the effectiveness of traffic engineering on one-way system the intersection Mambo Simpang Empat Pasar, which can cause congestion and accidents caused by shopping activities, and to find more careful traffic engineering solutions. This research uses a qualitative approach.